Implementasi Studi Kelayakan Bisnis pada Produk Ayam Geprek Ibu Ita - Vientiany, Dini; Purba, Fahrina Aulia; Sari, Mutia Indah; Damanik, Nayla Arnona (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the implementation of a business feasibility study in the culinary business of Ayam Geprek Rumahan Ibu Ita located in Medan Timur. A business feasibility study is conducted to assess whether the business is feasible to operate and develop, particularly from the marketing aspect. This research uses a qualitative descriptive method with data collection techniques including direct observation and interviews with the business owner. The analysis employs the Segmentation, Targeting, and Positioning (STP) approach as well as the marketing mix strategy (4P), which consists of product, price, place, and promotion. The results indicate that Ayam Geprek Rumahan Ibu Ita has a clearly defined market segment, namely students, workers, and surrounding communities who prefer spicy food at affordable prices. The targeting and positioning strategies are appropriate to consumer characteristics, supported by product variety, competitive pricing, a strategic location, and simple yet effective promotional activities through social media. Based on these findings, it can be concluded that Ayam Geprek Rumahan Ibu Ita is feasible to operate and has strong potential for further development.